Pre-analytical nonconformities in anatomic pathology: frequency and patient safety implications - Francis Rossetti Pedack; Daniela Corrêa Lamim Cardoso; Acir Alves Coelho Junior; Daniele de Oliveira; José Guilherme Jasper Pickler; Camila Barbosa; Hercilio Fronza Junior; Priscila Ferraz Franczak; Bruna Louise Silva; Paulo Henrique Condeixa de França; Karina Munhoz de Paula Alves Coelho (Surgical and Experimental Pathology, 2026)
Abstract Introduction The pre-analytical phase is recognized as the stage most susceptible to errors in the anatomic pathology laboratory process, potentially compromising diagnostic accuracy and patient safety. Monitoring nonconformities is an important strategy to identify process weaknesses and improve quality management. Objective To evaluate records of nonconformities (NC) in the pre-analytical phase of an anatomic pathology laboratory over a one-year period, with emphasis on events classified as patient safety risks. Methods A retrospective, cross-sectional study was conducted based on the analysis of records of pre-analytical NC over a one-year period. Events classified as opportunities for improvement were reviewed and categorized according to the institutional risk classification system. Results A total of 140,449 anatomic pathology examinations were processed during the study period, and 9,556 events were recorded as opportunities for improvement, corresponding to a nonconformity rate of 6.8%. Patient safety risks predominated (44.4%), followed by professional risks (34%) and administrative risks (15%). Among patient safety-related events, request form NC were the most frequent (57%), with missing lesion site information representing the most common inconsistency. Conclusion Systematic monitoring of N represents an important quality management tool in anatomic pathology laboratories. Failures in completing request forms, particularly the absence of lesion site information, represent a significant source of pre-analytical errors and highlight the need to improve communication and training of professionals involved in specimen collection and submission.